Educational Impacts and Cost-Effectiveness of Conditional Cash Transfer Programs in Developing Countries : A Meta-analysis (2013)
We meta-analyze enrollment, attendance and dropout impact and cost-effectiveness estimates from forty-two CCT program evaluations in fifteen developing countries. Average impacts and cost-effectiveness estimates for all outcomes in primary and secondary schooling are statistically different from zero, with considerable heterogeneity. CCT programs are, all else constant, most impactful and cost-effective for programs that, in addition to transfers to families, also provide supply-side complements-such as infrastructure or additional teachers. Impacts are also larger in programs with infrequent payments and more stringent schooling conditions, which aligns with previous singleprogram evidence. Impact and cost-effectiveness estimates from randomized research designs are smaller than those from observational studies